2021
DOI: 10.3390/medicina57070655
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence about Developmental Dysplasia of the Hip in Pregnancy

Abstract: In adults, developmental dysplasia of the hip (DDH) represents a spectrum of disorders. It is commonly found in women in routine orthopedic practice. Hip dysplasia is a leading precursor of joint laxity; when untreated, it can contribute to chronic modifications, such as thickening of the pulvinar and ligamentum teres (which can also elongate), hypertrophy of the transverse acetabular ligament, and osteoarthritis. DDH is presumed to be associated with alterations in pelvic morphology that may affect vaginal bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
9

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 84 publications
1
5
0
9
Order By: Relevance
“…Based on the information presented in Table 2 , it appears that the majority of children diagnosed with DDH had a normal nature of pregnancy. This finding is consistent with the results of other studies, which have also found that the incidence of DDH is not significantly associated with the nature of pregnancy [ 18 ]. The incidence of DDH is not significantly associated with the nature of pregnancy because the development of the hip joint occurs during fetal life and is influenced by factors that are largely independent of the mother’s pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the information presented in Table 2 , it appears that the majority of children diagnosed with DDH had a normal nature of pregnancy. This finding is consistent with the results of other studies, which have also found that the incidence of DDH is not significantly associated with the nature of pregnancy [ 18 ]. The incidence of DDH is not significantly associated with the nature of pregnancy because the development of the hip joint occurs during fetal life and is influenced by factors that are largely independent of the mother’s pregnancy.…”
Section: Discussionsupporting
confidence: 93%
“…The major drawback of Bernese osteotomy is technical difficulty because of a steep learning curve [ 15 ]. Steel osteotomy sometimes produces normal vaginal difficulty, but current literature shows it does not affect much in pregnancy and childbirth [ 16 ]. In our case, the patient was a male child.…”
Section: Discussionmentioning
confidence: 99%
“…Lower back pain is common, reported in 50% to 75% of patients, with 21% of patients reporting lower back pain as severe 15,16 . Sacroiliac joint pain is more common in women with a narrow ischial tuberosity diameter 19 . Pregnancy-related posterior pelvic pain often presents with ipsilateral buttock pain, stabbing in nature, which can refer to the thigh or knee and which is aggravated with axial loading of the femoral head on the posterior acetabulum 15 .…”
Section: The Native Hip In Pregnancymentioning
confidence: 99%